FORMULASI EKSTRAK KULIT BAWANG MERAH DAN ASAP CAIR TEMPURUNG KELAPA SEBAGAI PUPUK ORGANIK CAIR PADA TANAMAN BAYAM - Fitriyana, Fitriyana; Kurnyawaty, Noorma; Khotimah, Fitriani Khusnul; Salsabila, Andi Putri (Universitas 17 Agustus 1945 Samarinda, 2025)
Onion skin contains the minerals Ca, K, Mg, P, Zn and Fe as well as the hormones auxin and gibberellin. The hormones auxin and gibberellin are hormones that trigger plant growth and stimulate the growth of shoots and roots. The content of acidic groups in liquid smoke is also able to encourage growth and strengthen plant roots. Research on the combination of these two materials Liquid Organic Fertilizer (POC) is still not much done. This research is expected to increase plant growth and prevent plant diseases. Liquid Organic Fertilizer formulation is applied to spinach plants because spinach can be harvested in a short time, namely 25 days. The purpose of this study was to determine the effect of variations in the formulation of Liquid Organic Fertilizer and the frequency of application of Liquid Organic Fertilizer on the height and number of leaves of spinach plants. The research began with maceration of shallot skin using 96% ethanol solvent, then making Liquid Organic Fertilizer formulations by mixing coconut shell liquid smoke and shallot skin extract at a volume ratio of 1:0, 0:1, 1:1, 3:7 and 7:3. Each Liquid Organic Fertilizer formula was applied to spinach plants with a frequency of 0, 7 and 15 days. The data obtained were then analyzed using ANOVA and continued with Duncan's test. The results showed that the Liquid Organic Fertilizer formula had a significant effect on the height of spinach plants but the Liquid Organic Fertilizer formula did not have a significant effect on the number of spinach plant leaves. The best liquid organic fertilizer formula is 3:7. The frequency of application of Liquid Organic Fertilizer formula did not have a statistically significant effect on the height or number of leaves of spinach plants.